Biological Decontamination by Microplasma - Marius Gabriel Blajan; Alexandra Ciorita; Emanoil Surducan; Vasile Surducan; Kazuo Shimizu (Applied Sciences)
Dielectric-barrier-discharge microplasma has various applications such as flow control, surface treatment, air treatment, or biomedical applications. Microplasma was used for the inactivation of Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Bacterial strains spread on Petri dishes containing Nutrient Agar were treated with microplasma and, after incubation, inhibition zones were observed. By comparison, the experiments carried out with the already-grown bacteria on the Petri dish did not show any inhibitory response. Environmental air was used as discharge gas. The reactive oxygen and nitrogen species mainly carry out the inactivation process. A negative pulse voltage energized the microplasma electrodes. The microplasma treatment was the most potent against S. aureus, followed by E. coli, and P. aeruginosa, which was the least susceptible bacteria from the tested strains. An increase in the inhibitory efficiency was observed with the increase in discharge voltage from −1.5 kV to −1.7 kV. This research proved the efficiency of microplasma in biological decontamination and provides valuable insights of the inactivation of bacteria carried out with a technology that is suitable for easy integration and portability.